Decoration of metal oxide surface with 111 form Au nanoparticles using PEGylation. Issue 33 (21st May 2018) - Moon, Cheon Woo; Park, Jongseong; Hong, Seung-Pyo; Sohn, Woonbae; Andoshe, Dinsefa Mensur; Shokouhimehr, Mohammadreza; Jang, Ho Won
Abstract : Phase transfer in the ethanol-dichloromethane medium extinguished the limitation of the ligand exchange reaction on the gold (111) surface. High-coverage octahedral Au NP decoration on metal oxide semiconductors is achieved by the process. Abstract : The benefit of introducing gold nanoparticles is due to the plasmon relaxation process. The plasmon decay induces various phenomena such as near-field enhancement, hot electron injection, and resonance energy transfer. Shape-controlled octahedral gold nanoparticles can maximize the efficiency of these processes. For practical purposes, a high-coverage decoration method, comparable to physical vapor deposition on a metal oxide semiconductor nanostructure, is indispensable. However, the ligand exchange reaction to attach octahedral gold nanoparticles is limited in aqueous solution due to the inactivity of the gold (111) surface as a result of a densely-packed cetyltrimethylammonium bilayer structure. Herein, we report a controllable high-coverage surface decoration method of octahedral gold nanoparticles on the targeted semiconductor nanostructures via phase transfer by an organic medium with thiolated-polyethylene glycol. Our results deliver an innovative platform for future plasmonic gold nanoparticle applications.